FARMERS’ HOUSEHOLDS ECONOMIC SITUATION IN POLAND IN 2010–2017 - Sawicka, Janina; Biernat-Jarka, Agnieszka; Trębska, Paulina (Acta Scientiarum Polonorum. Oeconomia, 2019)
The aim of the research is to assess the financial situation of farm households in Poland in 2010–2017.The analysis of household finances, i.e. the value and structure of income as well as the method of their distribution, was performed. Despite a significant improvement in the living conditions of this group of people, the financial situation of farmers’ families was worse than of those who have other sources of income. Disposable income in households of farmers per person per month in 2017 amounted to PLN 1575.57 and was as much as PLN 420 higher than in the previous year. The ratio of the share of expenditure on food in total expenditure in 2017 was 31%. Aggregated data from studies of household budgets published annually by the Central Statistical Office constituted the basis of the information used as the sources and own surveys carried out in 2017 in 302 farmers households located in the Masovian Voivodeship.